What has been left after hosting the Formula 1 Grand Prix in Istanbul? - Gezici, Ferhan; Er, Serra (ELSEVIER SCI LTD, 2014)
Cities have been changing with the winds of globalization, which transforms economic structure from production to a more consumption-based economy. Especially since the 1990s, international events have increasingly become a new tool for attracting visitors, which bring revenue for the cities and enhance their competitiveness. Economically, it has been estimated that sporting events contribute 3% of the gross domestic product of OECD countries. Discussions in the literature related to sporting events generally focus on three main points: the organization and financing; the economic impacts; and the legacy of the events. The aim of this paper is to examine the hosting process of Formula 1 as a sporting event in Istanbul by taking into consideration the main discussion points. However, because the 2011 Formula 1 events no longer take place in Istanbul due to the lack of audience and very high costs, it has taught Istanbul some very important lessons. This paper argues that the public sector has failed to perform its most important role: proving the legitimacy of the event. Furthermore, the cost of Istanbul Park is huge, but the participation levels have been a lot lower than the Park's capacity and the legacy would be considered unfavorable. Most importantly, Formula l's lack of success in Turkey can lead to a better understanding of the main strategies of urban development over the last decade, how to stimulate economic growth and enhance new capital accumulation through the big projects within the most competitive cities. (c) 2014 Elsevier Ltd. All rights reserved.
Keywords: Sporting event; Organization; Impacts; Legacy; Formula 1; Istanbul; MEGA-EVENTS; Urban Studies